2019
DOI: 10.1186/s12876-019-0960-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of Small Intestinal Bacterial Overgrowth (SIBO) in Non-alcoholic Fatty Liver Disease (NAFLD) patients evaluated using Controlled Attenuation Parameter (CAP) Transient Elastography (TE): a tertiary referral center experience

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is an emerging disease, where it can progress to non-alcoholic steatohepatitis (NASH) and lead to liver cirrhosis or liver cancer. Small intestinal bacterial overgrowth (SIBO) has been hypothesized to play an important role in NAFLD development and progression, however, there is still conflicting data about this phenomenon. Transient Elastography (TE) examination using controlled attenuation parameter (CAP) has been validated for liver disease progression ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…10,21,22,[24][25][26]28 We included patients only with both FibroScan and LB diagnosed NAFLD in our analysis. In a part of the previous studies, NASH was diagnosed via non-invasive methods (US abdomen, liver enzymes and transient elastography), 10,22,23 while in other studies, NASH was diagnosed solely based on LB. 21,[24][25][26] According to recent studies, TE is a suitable method for non-invasive detection and staging of steatosis and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…10,21,22,[24][25][26]28 We included patients only with both FibroScan and LB diagnosed NAFLD in our analysis. In a part of the previous studies, NASH was diagnosed via non-invasive methods (US abdomen, liver enzymes and transient elastography), 10,22,23 while in other studies, NASH was diagnosed solely based on LB. 21,[24][25][26] According to recent studies, TE is a suitable method for non-invasive detection and staging of steatosis and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al used bioinformatics to find that the part encoded by the N -acyl amide gene of human symbiotic bacteria interacts with GPR119 by mimicking human lipid signaling molecules, such as 2-OG, showing a way to treat metabolic diseases thought to regulate intestinal microbes [ 110 ]. Fitriakusumah et al found that MAFLD is significantly associated with the overgrowth of intestinal flora [ 111 ]. The overgrowth of intestinal flora in MAFLD patients can cause changes in the permeability of the intestinal mucosa and the destruction of tight junction structures, resulting in lipopolysaccharides (LPS) and other substances entering the blood, and they interact with Toll-like receptors through NF-kB and other pathways, producing inflammatory mediators and triggering chronic inflammation and insulin resistance (IR) [ 112 , 113 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyols are around 25%-100% as sweet as sugar and include erythritol, hydrogenated starch hydrolysates (sometimes listed as maltitol syrup, hydrogenated glucose syrup, polyglycitol, polyglucitol, or simply HSH), isomalt, lactitol, maltitol, mannitol, sorbitol, and xylitol. All of them are considered safe for human consumption as long as they are consumed within the acceptable daily intake [6]. This safety was claimed by the European Food Safety Authority (EFSA) except for cyclamate, which is not approved by the US Food and Drug Administration [1,7,8].…”
Section: Introductionmentioning
confidence: 99%